High‐Density Mapping of Resistance QTL Toward Phytophthora sojae, Pythium irregulare, and Fusarium graminearum in the Same Soybean Population. Issue 5 (1st September 2016) - Stasko, Anna K.; Wickramasinghe, Damitha; Nauth, Brittany J.; Acharya, Bhupendra; Ellis, Margaret L.; Taylor, Christopher G.; McHale, Leah K.; Dorrance, Anne E.
Abstract : Phytophthora sojae Kaufm. and Gerd., Pythium irregulare Busiman, and Fusarium graminearum Schwabe [teleomorph: Gibberella zeae (Schwien.) Petch] are important pathogens of soybean [ Glycine max (L.) Merr.] and are all capable of causing seed rot, damping‐off, and root rot. The objective of this study was to identify quantitative trait loci (QTL) for resistance to Py. irregulare and to refine previously mapped QTL for resistance to P. sojae and F. graminearum in a larger, more advanced 'Conrad' × 'Sloan' F9:11 recombinant inbred line population. The population was mapped with 1032 single nucleotide polymorphisms from the SoySNP6K BeadChip and 31 polymerase chain reaction–based molecular markers. Families were evaluated for resistance response to three isolates of P. sojae, one isolate of Py. irregulare, and one isolate of F. graminearum . A total of 10, 2, and 3 QTL and suggestive QTL were found that confer resistance to P. sojae, Py. irregulare, and F. graminearum, respectively. Individual QTL explained 2 to 13.6% of the phenotypic variance. Quantitative trait loci for resistance toward both Py. irregulare and F. graminearum colocalized on chromosome 19. This resistance was contributed by Sloan and was juxtaposed to a QTL for P. sojae with resistance contributed from Conrad. Alleles for resistance to different pathogens contributed from different parents in the same region; the number of unique QTL for each pathogen and the lack of correlation of resistance suggest that different mechanisms are involved in resistance toward P. sojae, Py. irregulare, and F. graminearum .